Control of rhizome growth in Alstroemeria - Bond, Steven (1991)
Increases of temperature in the range from 8 to 18°C in vivo, significantly enhanced the dry weights of lateral rhizomes, roots and shoots. At the higher temperatures dry weight production was often seen to decrease. Decreases in irradiance from 100 to 50 per cent in vivo, produced significant decreases in the dry weights of lateral rhizomes, roots and shoots. In contrast, the numbers of lateral rhizomes, tubers and shoots were largely unaffected by temperature and irradiance treatments. Day length treatments of 8 to 16 hours light in a 24 hour period in vivo produced few significant changes in either the dry weights or numbers of plant parts produced. However, day length had a strong influence over the time of flowering. For maximum rhizome production a temperature of between 13 and 18°C, a high irradiance and a short day length were required.